Structure and community dynamics of a natural and a disturbed tropical seasonal forest in Thailand - Yarwudhi, C.; Kobayashi, S.; Kutintara, U.; Takahashi, M.; Marrod, D.; Hirai, K.; Eiadtong, W.; Tanaka, H.; Nakashizhuka, T. (1997)
Dynamics of tree populations were studied from 1992 to 1995 in 4 ha permanent plots placed both in a natural and a disturbed tropical seasonal forest in Mae Klong Watershed Research Station, Kanchanaburi, Western Thailand. In the natural forest, the recruitment, mortality, gain and loss rate in basal area (trees > 5 cm dbh) during the first 2 years were 10.50 % yr-1, 1.52 % yr-1 and 1.51 % yr-1, respectively. High recruitment rate compared with the other temperate and tropical forests (ca. 1-2 % yr-1) was caused by the death of a bamboo species a few years before. Forest fires which occured after that also affected the high recruitment rate. The spatial pattern of recruited trees was concentrated at the area where the bamboo died and the forest fire occured. In a disturbed forest, the recruitment, mortality, gain and loss rate in basal area during 3 years were in the range of 25.8 - 51.7 % yr-1, 6.9 - 55.5 % yr-1, 41 - 64 % yr-1 and 5.6 - 57.6 % yr-1, respectively. Higher recruitment and growth rate of trees in a disturbed forest compared with those in a natural forest greatly contributed to the recovery of forest biomass. Contrary to the annualy stable gain in basal area, mortality rate and loss rate in basal area were highly variable among years caused by the opportunistic occurence of fire. Fire regime greatly affects the dynamics both in a natural forest and a disturbed forest.